Peculiarities of interrelation between satisfaction with the obligatory military service and military readiness - Žakaitis, Povilas; Rugevičius, Mindaugas (Psichologija, 2004)
The present investigation examined the relations between servicemen satisfaction with the military service, demographic variables and military readiness. The study also assessed the dynamic changes of servicemen satisfaction with the military service. Participants: 211 servicemen of obligatory military service in N battalion aged 19–24 years took part. The servicemen satisfaction with the military service was assessed by the Job-Related Affective Well-Being Scale (JAWS) and Job Satisfaction Scale (JSS). Both scales were translated into Lithuanian language with the permission of P. Spector. The servicemen were evaluated twice with JAWS – on the 3rd and 12th months of the service. At the end of 3rd month of the military service servicemen were evaluated with JSS. 22 indicators of the military readiness were taken as follows: 2 grades of physical fitness tests; 8 grades of Basic Military Training (BMT) Programme; 6 scores of tactics field training performance and 6 scores that generalize the servicemen military readiness during the whole period of the military service, which were presented by the section commanders. Significant relationships were revealed between the level of the servicemen emotional well-being that was evaluated on the 3rd month and the level of the emotional well-being at the end of the military service (r = 0.63; p < 0.01). The results indicated that the scores of all three evaluations of servicemen satisfaction with the military service are significantly higher among the servicemen descended from countries as compared with the servicemen descended from towns. The differences of satisfaction indicators were not significant among servicemen with higher and lower education. In the result of applying the nonhierarchical clustering k-means method three estimates of satisfaction with the military service grouped the servicemen in two clusters. One group consisted of 113 servicemen of relatively higher satisfaction. The other group consisted of 98 servicemen of relatively lower satisfaction. Comparisons between these groups by means of Mann-Whitney criterion of ranks sum for independent samples showed that the scores of military readiness indicators were higher in the group with higher satisfaction. More than 50% (12 from 22) of all military readiness indicators differed significantly in these groups. BMT grades as compared revealed that the group with higher satisfaction scored significantly higher on 5 subjects: tactical knowledge (p < 0.001), topography, shooting and musketry, military communication and weapon of mass destruction (p < 0.05). Ratings of tactics field performance as compared differ significantly in three evaluations: tactical proficiency, topography and ability to act in team (p < 0.05). Section commanders evaluated as better the Professional readiness and relations with the service peers in the group of the higher satisfaction with the military service (p < 0.05). To conclude, it seems that the servicemen satisfaction is quite stable during the whole period of the military service. This seems to suggest that the first months of obligatory military service could predict further dynamic changes of the servicemen satisfaction. The satisfaction with the military service is related with the scores of the military readiness. It let us assume that satisfaction with the military service influences in some degree the formation of the servicemen skills and abilities to perform their functions.